Somatic embryogenesis as a tool for virus elimination in Croatian indigenous grapevine cultivars - Malenica, Nenad (Array, 2020)
Most Croatian indigenous grapevine cultivars and vineyards are infected with a few dominant viruses. The goal of this study was to establish somatic embryogenesis as an efficient method for virus elimination from valuable Croatian cultivars and creating a reliable source of healthy plants. Somatic embryogenesis was induced from immature anthers and somatic embryogenesis-derived plantlets for seven indigenous cultivars were successfully regenerated. This procedure led to the elimination of viruses GFLV, GLRaV-1, GLRaV-3 and GFkV that were initially detected in the field-grown cultivars ‘Plavac mali’ and ‘Babica’ with an elimination success of at least 30%. The described method has the potential for production of virus-free rooted plantlets for all economically important cultivars or superior cultivar clones and for the establishment of a steady source of certified virus-free planting material.